pengaruh pemberian beberapa stimulator perombak bahan organik terhadap pengomposan tandan kosong kelapa sawit - hutapea, leo cardi (Fakultas Pertanian Universitas Tanjungpura, 2016)
Abstract This research is conducted to acknowledge the best stimulator of all organic-reorganized stimulators, EM-4, Starbio, Orgadeg, and chicken's feces. This research applies a complete random design by using SPSS 20 for window, consisting of several kinds of organic-reorganized stimulators by controlling S0, S1 (EM-4), S2 (chicken's feces), S3 (starbio), S4 (orgadeg), and this research is 5 times retested containing 25 plot tests. The result of this research shows that by giving organic stimulators can fasten the process of decomposing for 20 days decomposing increases the temperature until 55 on S4 (chicken's feces), decomposing for 40 days increases pH, 9 on S2 (chicken's feces), the reduce of C/N-ratio 14,23 on the last decomposing on S4 (orgadeg). The increase of N on S1 (EM-4) for 2,93%, the increase of P for 1,85% on S4 (orgadeg), the increase of (K) for 2,72% on (S1) EM-4.